Molecular biological subtypes of breast cancer in BRCA1 mutation carriers - N. I. Pospekhova; D. A. Golovina; M. G. Filippova; A. V. Semyanikhina; S. L. Dranko; A. M. Danishevich; A. M. Stroganova (Успехи молекулярной онкологии, 2021)
Background. According to the literature, BRCA1-associated breast cancer (BC) most often belongs to the triple negative (TNBC) molecular subtype. The data on the contribution of other molecular subtypes to this group of patients differ among different studies.The study objective is to evaluate the frequency of different tumor molecular subtypes in BC patients with BRCA1 gene mutation treated in N. N. Blokhin National Medical Research Center of Oncology in the period from 2017 to 2020.Materials and methods. The study included BC patients with a mutation in the BRCA1 gene (n = 209) identified as a result BRCA1 mutation screening of patients with BC. DNA diagnostics was carried out on blood samples of patients using the real-time polymerase chain reaction method. After analyzing the patients primary documentation clinical and morphological data were taken into account: the age of diagnosis, the stage of the disease, the results of immunohistochemical studies (estrogen receptor status, progesterone receptor status, HER2 expression, Ki-67 proliferation index). The assignment to the particular molecular tumour subtypes was performed according to estrogen receptor status, progesterone receptor status, HER2 status and Ki67 value.Results. Clinical and pathomorphological data of 209 patients with BRCA1-associated BC were analyzed. The age at diagnosis ranged from 23 to 72 years, the median age was 40 years, the mean age was 41.46 ± 9.82 years. BC associated with BRCA1 was found to be TNBC in 71.3 % and luminal B, HER2 negative (LumB–) in 19.1 % of the cases. Other tumour subtypes were much less common: luminal B, HER2 positive (LumB+) in 7.2 %, luminal A (LumA) in 1 % and HER2-positive (HER2+) in 1.4 % of the cases. The frequency of subtypes was estimated in different age groups (1st – patients 23–34 (n = 53), 2nd – 35–49 (n = 111), and 3rd – 50–72 (n = 45) years old). TNBC frequency was 81.1 % in the 1st group, 73.9 % in the 2nd and 53.4 % in the 3rd group; LumB– frequency was 15.1, 15.3 and 33.3 % respectively. Using the Fisher test it was shown that the differences in frequencies were statistically significant between groups 1st and 3 rd, as well as between groups 2 nd and 3 rd (p <0.05).Conclusion. TNBC was the main molecular subtype in all age groups of BC patients with BRCA1 germinal mutation, TNBC frequency was lower in the older age group. LumB– subtype was also common in BRCA1-associated tumors especially in older women.